When less is more: the forbidden fruits of gene repression in the adult β‐cell. Issue 6 (22nd November 2012) - Pullen, T. J.; Rutter, G. A.
Abstract Outside of the biological arena the term 'repression' often has a negative connotation. However, in the pancreatic β‐cell a small group of genes, which are abundantly expressed in most if not all other mammalian tissues, are highly selectively repressed, with likely functional consequences. The two 'founder' members of this group, lactate dehydrogenase A (Ldha) and monocarboxylate transporter‐1 (MCT‐1/Slc16a1), are inactivated by multiple mechanisms including histone modifications and microRNA‐mediated silencing. Their inactivation ensures that pyruvate and lactate, derived from muscle during exercise, do not stimulate insulin release inappropriately. Correspondingly, activating mutations in the MCT‐1 promoter underlie 'exercise‐induced hyperinsulinism' (EIHI) in man, a condition mimicked by forced over‐expression of MCT‐1 in the β‐cell in mice. Furthermore, LDHA expression in the β‐cell is upregulated in both human type 2 diabetes and in rodent models of the disease. Recent work by us and by others has identified a further ∼60 genes which are selectively inactivated in the β‐cell, a list which we refine here up to seven by detailed comparison of the two studies. These genes include key regulators of cell proliferation and stimulus‐secretion coupling. The present, and our earlier results, thus highlight the probable importance of shutting down a subset of 'disallowed' genes for the differentiated function of β‐cells, and implicate previously unsuspected signalling pathways in the control of β‐cell expansion and insulin secretion. Targeting of deregulated 'disallowed' genes in these cells may thus, in the future, provide new therapeutic avenues for type 2 diabetes.